Metabolic disturbances in hypertensive SHR rats - Gancheva, О. V.; Kolesnik, Yu. М.; Аbramova, Т. V.; Samoylenko, N. Yu.; Abramov, A. V.; Ганчева, Ольга Вікторівна; Колесник, Михайло Юрійович; Абрамова, Тетяна Вікторівна; Самойленко, Н. Ю.; Абрамов, Андрій Володимирович (My University, 2013)
The aim of research was to determine the parameters of carbohydrate and lipid metabolism biochemical indices in hypertensive SHR rats. The research was carried out in 20 male Wistar rats and 47 SHR rats of 5-6 months old. The concentration of glucose, insulin, leptin, lipids, triglycerides and cholesterol in the blood serum has been determined by biochemical methods. The intraperitoneal glucose tolerance test has been carried out. The results of the research have shown that according to the basal glycemia level in SHR rats 32% of animals have fasting normoglycemia, 38% – disturbed glucose tolerance, 30% – fasting hyperglycemia. The glucose tolerance test in normoglycemic SHR rats resulted in hyperglycemia significantly exceeding the renal reabsorption threshold, and the indices of glycemia didn’t reach the normoglycemia range by the 90-th minute of the test. Disturbance of glucose tolerance and fasting hyperglycemia in SHR rats was observed along with progressive increase of the animals’ body weight by 62-75%, and combined with increase of the leptin and insulin concentration, HOMA-IR index, as well as correlated with increase of the concentration of lipids, triglycerides and cholesterol in blood. disturbances of the hormonal and cytokine balance were also revealed in these animals; they were characterized by a high level of corticosteroids and pro-inflammatory cytokines (interleukin-6, tumor necrosis factor alpha) in blood. Such disturbances of neuroendocrine, hormonal, cytokine, carbohydrate and lipid metabolism were observed in hypertensive SHR rats definitely demonstrate the typical signs of metabolic disturbances by the diabetic pattern, and, in our opinion, allow to consider hypertonic disease as a predictor of diabetes mellitus type 2 development.Метою дослідження було визначення параметрів біохімічних показників вуглеводного та ліпідного гомеостазу у гіпертензивних щурів лінії SHR. Дослідження проведено на 20 самцях щурів лінії Wistar та 47 щурах лінії SHR віком 5-6 міс. Біохімічними методами визначали концентрацію у сироватці крові глюкози, інсуліну, лептину, ліпідів, тригліцеридів і холестерину. Проводили внутрішньоочеревинно тест толерантності до глюкози. За рівнем базальної глікемії серед щурів лінії SHR 32% становлять тварини з нормоглікемією, 38% – з порушеною толерантністю до глюкози і 30% – з гіперглікемією. Проведення тесту толерантності до глюкози у нормоглікемічних щурів лінії SHR призводило до гіперглікемії, що значно перевищувала поріг ниркової реабсорбції глюкози, причому на 90-й хвилині тесту показники глікемії не досягали нормоглікемічного діапазону. Порушення толерантності до глюкози і формування гіперглікемії натще у щурів лінії SHR відбувалося на тлі прогресуючого збільшення маси тіла тварин на 62-75%, поєднувалося з підвищенням концентрації інсуліну, лептину та індексу інсулінорезистентності HOMA, а також корелювало з підвищенням концентрації в крові ліпідів, тригліцеридів і холестерину. На цих тваринах також було продемонстровано дисбаланс гормонів та цитокінів, які характеризувалися високим рівнем вмісту кортикостероїдів та протизапальних цитокінів крові. Таке порушення нейроендокринного, гуморального, цитокінного, вуглеводного та ліпідного метаболізму спостерігалося у гіпертензивних щурів лінії SHR, які характерні для діабету 2-го типу.
Метаболічні порушення у гіпертензивних щурів лінії SHR
Метаболические нарушения у гипертензивных крыс линии SHR
Keywords: arterial hypertension; carbohydrate metabolism; lipid metabolism; артеріальна гіпертензія; вуглеводний обмін; ліпідний обмін; артериальная гипертензия; углеводный обмен; липидный обмен